Framing of LGBT in Online Newspapers in Malaysia - Ting, Su Hie; Audrea, Johnson; Jerome, Collin (Asian Scholars Network (ASNET), 2020)
In Malaysia, Lesbian, Gay, Bisexual dan Transgender (LGBT) face moral sanctions and legal challenges because it is prohibited by Islam and not condoned by other major religions. A search using Google Trends show that there was a spike of interest on “LGBT in Malaysia” in 2009 and 2019, but there has been sustained interest since 2014. The present study examined framing of LGBT in four online newspapers in Malaysia. The specific objectives of the study were to determine the percentage of episodic and thematic framing in the newspapers, and to compare the topics that are reported in LGBT news. A total of 60 newspaper articles published in 2019 were identified from Astro Awani, Free Malaysia Today, Malaysiakini and The Star Online. The analysis showed that 81.67% of the articles were episodic frames and 18.33% were thematic frames. The four newspapers differ in the proportion of episodic and thematic articles on LGBT. The main events related to LGBT were the Women’s Day March in Kuala Lumpur on 9 March 2019 and the vote against the International Labour Organisation agreement. Many news articles reported politicians, religious leaders, activists and companies expressing either support or condemnation of LGBT. Over half (61.67%) of the articles were on LGBT news stories in Malaysia while other articles reported LGBT-linked persons or events in other countries. The findings suggest caution in news on LBGT, with newspapers treading a thin line between affirming human rights and taking the official position of the country on LGBT.